1994
DOI: 10.1111/j.1432-1033.1994.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Biochemical Characterization of Human Protein Kinase C‐θ

Abstract: In this study, the recently identified human protein kinase C-6 (PKC-8) isoform has been biochemically characterized in detail. An antiserum raised against the unique V3 domain of PKC-O identified an 80-kDa protein in all human T-cell lines tested, in erythroleukemia K562 cells and in histiocytic lymphoma U-937 cells, but not in a B-lymphoma line (Raji) or in several melanoma, carcinoma, schwanoma or astrocytoma lines, confirming, at the protein level, its predominant expression in hematopoietic cell lines, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
100
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 35 publications
9
100
0
Order By: Relevance
“…Our data demonstrating a minimal contribution of DAG to the PS activation of PKC-phosphorylation of moesin is consistent with the findings of Baier et al (29), who showed a similar minimal effect of phorbol 12-myristate 13-acetate to the PS activation of PKC-. A comparable pattern has been observed with PKC-␦ phosphorylation of the ␥ chain of the IgE receptor, where the rate of threonine phosphorylation was increased 2.5-fold using PI compared with PS, whereas the effect of PG was not tested (53).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our data demonstrating a minimal contribution of DAG to the PS activation of PKC-phosphorylation of moesin is consistent with the findings of Baier et al (29), who showed a similar minimal effect of phorbol 12-myristate 13-acetate to the PS activation of PKC-. A comparable pattern has been observed with PKC-␦ phosphorylation of the ␥ chain of the IgE receptor, where the rate of threonine phosphorylation was increased 2.5-fold using PI compared with PS, whereas the effect of PG was not tested (53).…”
Section: Discussionsupporting
confidence: 82%
“…8, maximal kinase activity was obtained using PG and His 6 -moesin, whereas the kinase activity toward MBP was lipidindependent, and histone H1 phosphorylation was minimal. These results are consistent with previous findings of PKCusing an MBP-derived peptide and histone H1 (29).…”
Section: Fig 6 Partial Purification Of Pkc-from Aml Cellssupporting
confidence: 83%
See 2 more Smart Citations
“…Recruitment of PKC-to the membrane is necessary for its activation and involvement in signaling (24). Our group has previously used immunofluorescent methods to show, at the single-cell level, a decline with age in the proportion of CD4 ϩ and CD8 ϩ T cells that mobilize PKC-to the T cell/APC interface in responses triggered by anti-CD3 hybridoma cells (25).…”
mentioning
confidence: 99%